Yiqi Huazhuo decoction increases insulin secretion in type 2 diabetic rats by regulating the pancreatic GPR40-IP3R-1 signaling pathway - Wu, Dongjiao; Weng, Siying; Xu, Shuyi; Li, Yan; Zhou, Jianyang (Frontiers in Pharmacology, 2023)
Objective: Yiqi Huazhuo Decoction (YD) reduces blood glucose, glycated hemoglobin, body weight, and insulin resistance in patients with type 2 diabetes mellitus (T2DM), but its exact mechanisms are unknown. This study investigated the therapeutic effects and mechanisms of YD on impaired insulin secretion in T2DM rats. Methods: T2DM rats were randomized to the model, YD-lo (15 mg/kg/d YD, 10 weeks), YD-hi (30 mg/kg/d YD, 10 weeks), positive drug (TAK-875), and healthy control groups. The rats underwent an oral glucose tolerance test (OGTT), glucose-stimulated insulin secretion (GSIS) test, and serum lipid measurements. High-fat and high-glucose-injured RIN-m5f cells were treated with YD (30 or 150 mg/ml) for 48 h. GPR40 and IP3R-1 expression levels were determined by immunofluorescence, qRT-PCR, and western blot. Results: Compared with the model group, the OGTT area under the curve (AUC) in the YD-hi group was decreased by 26.7%, the insulin release test (IRT) AUC in the YD-hi group was increased by 45.9%, and the GSIS AUC was increased by 33.9% (P<0.05). Compared with the model cells, the insulin secretion after glucose stimulation in the YD-hi group was increased by 24.5%, similar to the TAK-875 group (23.1%) (P>0.05). GPR40 and IP3R-1 mRNA in the model cells were decreased by 49.5% and 51.2% compared with the control cells (P<0.05). In the YD-hi group, GPR40 and IP3R-1 mRNA levels were increased by 58.1% and 39.3% (P<0.05), similar to the TAK-875 group. The changes in protein expression were similar to mRNA. Conclusions: YD promotes insulin secretion from pancreatic islet β-cell in T2DM rats by regulating the GPR40-IP3R-1 pathway, thereby reducing blood glucose.